Parents’ satisfaction with their children’s dental care provided by dental student - Harun, Nor Asilah; Abu Kassim, Noor Lide; Muhannad Kashmoola, Sayfaldeen; Ghazali, Ahmad Badruddin (2016)
Introduction: In dental school, clinical year students are treating patients under close supervision of trained supervisors as part of their training. The concern of the dental school is to teach the students about providing good quality dental care. Islam is really emphasis on the higher quality possible especially in serving the other people needs and for those who requires help. The feedback from the patient is an indicator so that the quality of the service can be assessed, improved and as a good predictor for the patient compliance. Aim: To evaluate parent’s satisfaction with their children’s dental care provided by undergraduate dental student at the Student’s Polyclinic, Kulliyyah of Dentistry, IIUM. Materials and Method: A self-administered questionnaire with questions on accessibility and availability, physical environment, service quality, interpersonal communication, financial, efficacy and treatment outcome were distributed to parents who attending their children dental treatment from January 2013 to October 2013. Data collected were analyzed using Rasch Analysis, Independent Sample T-Test, and Mann-Whitney Test. Results: 70 questionnaires were completed and analysed. The result showed that the average level of parental satisfaction was high. The parents were most satisfied with students’ interpersonal communication and the physical environment of the clinic. The level of satisfaction of parents of female children were higher than parents of male children although the difference was not significant. No significant differences were found in relation to which parent accompanied the child for treatment and the parent’s education level. However, parent’s level of satisfaction is associated with type of occupation, where non-health-related workers expressed higher level of satisfaction (p=0.014). Conclusion: Parents were generally satisfied with the care that their children received mainly with the aspect of students’ interpersonal communication and physical environment of the clinic. The results also indicated that level of satisfaction was associated with the nature of occupation. Keywords: parent’s satisfaction, pediatric dentistry treatment